Getting published in academic journals : navigating the publication process - Paltridge, Brian; Starfield, Sue, 1952- (University of Michigan Press, 2016)
The pressure on graduate students and new PhDs to publish their work continues to grow with writing and publishing considered an important measure of career success within the academy. There is, however, more to the process of getting published than those who are new to the process initially realize. The aim of this guide is to clarify the process and offer advice. Getting Published in Academic Journals is written for graduate students and newly graduated PhDs who want to publish their research in peer-reviewed academic journals. Getting Published in Academic Journals draws on the experiences of the authors as editors of peer-reviewed journals, as teachers of writing-for-publication courses and workshops, as researchers of the scholarly publication process, as reviewers of hundreds of articles, and as published authors. The book is written to be used in courses and workshops on publishing, as a supplement to the books in the revised and updated English in Today's Research World (Swales & Feak) series, and as a stand-alone guide for academic writers working independently. Book jacket.